2020
DOI: 10.2147/cmar.s260943
|View full text |Cite
|
Sign up to set email alerts
|

<p>MDM2-C Functions as an E3 Ubiquitin Ligase</p>

Abstract: Background Mouse double minute 2 (MDM2) is an E3 ubiquitin ligase that is over-expressed in many cancers and regulates target proteins through ubiquitination. Full-length MDM2 (MDM2-FL) is best known for targeting wild-type p53 for degradation by the proteasome, but the functions of the many splice variants of MDM2 are under-explored. The three well-studied alternative MDM2 isoforms are MDM2-A/ALT2, MDM2-B/ALT1, and MDM2-C/ALT3. MDM2-A and MDM2-B are capable of down-regulating MDM2-FL activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…As the T24 cell line contains the mutant p53, while the EJ cell line expresses the wild-type p53, the results suggested that circNUDT21 may exert its oncogenic function through the MDM2-p53 pathway in bladder cancer, regardless of the p53 mutation status. Our finding is supported by Kim and colleagues, 30 who found that MDM2-C has E3 auto-ubiquitin ligase activity, which can promote the ubiquitination of both wild-type and mutant p53.…”
Section: Discussionsupporting
confidence: 86%
“…As the T24 cell line contains the mutant p53, while the EJ cell line expresses the wild-type p53, the results suggested that circNUDT21 may exert its oncogenic function through the MDM2-p53 pathway in bladder cancer, regardless of the p53 mutation status. Our finding is supported by Kim and colleagues, 30 who found that MDM2-C has E3 auto-ubiquitin ligase activity, which can promote the ubiquitination of both wild-type and mutant p53.…”
Section: Discussionsupporting
confidence: 86%
“…91 MDM2 is highly expressed in various types of cancer with specific isoforms such as MDM2-C being present in breast cancer and liposarcoma tissue and cell lines. 90 Expression of MDM2 is also increased in lung tissue of patients with idiopathic pulmonary arterial hypertension and mice with induced pulmonary hypertension. 72 This upregulation of MDM2 is associated with a downregulation in ACE2 levels in lung tissues and the mechanism seems to involve binding to ACE2 at lysine site K788.…”
Section: Mouse Double Minute 2 Homologmentioning
confidence: 99%
“…87,88 One mechanism by which MDM2 dampens p53 levels is through the ubiquitin-proteasome system. 89 MDM2 is composed of 491 amino acids 90 and the RING domain at the C terminus is the region that performs the E3 ligase functions. 91 MDM2 is highly expressed in various types of cancer with specific isoforms such as MDM2-C being present in breast cancer and liposarcoma tissue and cell lines.…”
Section: Mouse Double Minute 2 Homologmentioning
confidence: 99%
“…Of note, despite the increase in p53 ubiquitination, heterodimers of MDM2-B and full-length MDM2 even increased p53 activity [ 99 , 100 ]. More recently, it was found that MDM2-C also has E3 activity and ubiquitinates wild-type and mutated (R273H) p53 [ 101 ]. However, it was not determined whether this ubiquitination of p53 by MDM-C leads to p53 degradation.…”
Section: E3s That Target Wild-type P53mentioning
confidence: 99%